Using the near field optical trapping effect of a dielectric metasurface to improve SERS enhancement for virus detection - Cameron F. Kenworthy (Nature Portfolio, 2021)
Abstract In this paper, we report the effect of optical trapping on the enhancement factor for Raman spectroscopy, using a dielectric metasurface. It was found that a higher enhancement factor (up to 275%) can be obtained in a substrate immersed in water, where particles are freee to move, compared to a dried substrate, where the particles (radius $$r=9$$ r = 9  nm, refractive index $$n=1.58$$ n = 1.58 ) are fixed on the surface. The highest enhancement is obtained at low concentrations because, this case, the particles are trapped preferentially in the regions of highest electric field (hotspots). For high concentrations, it was observed that the hotspots become saturated with particles and that additional particles are forced to occupy regions of lower field. The dielectric metasurface offers low optical absorption compared to conventional gold substrates. This aspect can be important for temperature-sensitive applications. The method shows potential for applications in crystal nucleation, where high solute supersaturation can be achieved near the high-field regions of the metasurface. The high sensitivity for SERS (surface-enhanced Raman spectroscopy) at low analyte concentrations makes the proposed method highly promising for detection of small biological particles, such as proteins or viruses.